A review on adsorption characteristics and influencing mechanism of heavy metals in farmland soil. Issue 6 (25th January 2023) - Yu, Hanjing; Li, Chenchen; Yan, Jin; Ma, Yaoqiang; Zhou, Xinyu; Yu, Wanquan; Kan, Huiying; Meng, Qi; Xie, Ruosong; Dong, Peng
Abstract : The accumulation of heavy metals in soil and crops is considered to be a severe environmental problem due to its various harmful effects on animals and plants. Abstract : The accumulation of heavy metals in soil and crops is considered to be a severe environmental problem due to its various harmful effects on animals and plants. Soil adsorption is an essential characteristic of mud, which is the fundamental reason for soil to have a specific self-purification capacity and environmental capacity for heavy metals. The adsorption of heavy metals by soil reduces the uptake of these pollutants by crops, thereby limiting food contamination. Therefore, the adsorption of heavy metals in crop soils was taken as the primary research object. Based on the entire reading of the literature, the previous research results were compared and discussed from the four aspects of heterogeneity, physical and chemical properties, competitive adsorption, and external factors. The influencing mechanism of heavy metal adsorption characteristics in soil was reviewed. Finally, suggestions and prospects for future research on heavy metal adsorption were put forward.